Volume 2: Emissions Control Systems; Instrumentation, Controls, and Hybrids; Numerical Simulation; Engine Design and Mechanical 2017
DOI: 10.1115/icef2017-3533
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Ignition and Combustion of a Pilot Ignited Natural Gas Jet Using Numerical Simulation Based on Detailed Chemistry

Abstract: In this paper, a multidimensional computational fluid dynamics (CFD) model coupled with detailed chemistry calculations was used to analyze dual-fuel combustion based on high pressure direct injection of natural gas. The main focus was to analyze the capability of predicting pressure curve and heat release rate (HRR) for different injection strategies. Zero-dimensional homogeneous constant volume reactor calculations were used to select a reaction mechanism for the temperature range below 800 K. As the best-pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…8 that the burning region can be clearly distinguished from the unburning region. According to a previous study [63], the initial combustion stage of the HPDI engine belongs to the premixed combustion, which can be demonstrated In summary, the 35-step mechanism can reproduce the ignition delay times of n-heptane at all research temperatures, while the 27-step mechanism gives reasonable predictions of ignition delay times for n-heptane at high temperatures. Both of these two mechanisms give well predictions of ignition delay times for methane.…”
Section: Mechanism Validation In a Marine Enginesupporting
confidence: 55%
“…8 that the burning region can be clearly distinguished from the unburning region. According to a previous study [63], the initial combustion stage of the HPDI engine belongs to the premixed combustion, which can be demonstrated In summary, the 35-step mechanism can reproduce the ignition delay times of n-heptane at all research temperatures, while the 27-step mechanism gives reasonable predictions of ignition delay times for n-heptane at high temperatures. Both of these two mechanisms give well predictions of ignition delay times for methane.…”
Section: Mechanism Validation In a Marine Enginesupporting
confidence: 55%
“…The combustion is calculated using the SAGE Detailed Chemical Kinetics Solver with reaction mechanism resulting from a combination of the GRI3.0 33 for methane and the Chalmers53 n-heptane mechanisms. The Chalmers 53 has been giving good results for methane-diesel HPDF in 34,35 and the GRI3.0 is validated in literature – giving satisfying results for the laminar burning velocity in ammonia combustion. 10,36…”
Section: Methodsmentioning
confidence: 76%
“…They found that a strong interaction between diesel spray and natural gas jet led to the delayed pilot ignition but the rapid and stable onset of the gas jet combustion process. By employing both the optical diagnostics and numerical modeling, Jud et al 26 investigated the ignition and combustion of a pilot ignited NG combustion process on a rapid compression machine. They found that an early NG start of ignition (SOI) timing results in a premixed-combustion process at the initial combustion stage.…”
Section: Introductionmentioning
confidence: 99%